Evidence that methoxypyrazine accumulation is elevated in Shiraz rachis grown on Ramsey rootstock, increasing 'green' flavour in wine. (27th March 2022) - Capone, D.L.; Francis, I.L.; Clingeleffer, P.R.; Maffei, S.M.; Boss, P.K.
Abstract: Background and Aims: 'Green' sensory characters in Shiraz wines were observed in wines produced from different rootstocks. The compounds responsible were investigated as these attributes are generally seen as negative. Methods and Results: GC/MS‐olfactometry and stable isotope dilution analysis methods were used to identify and quantify a range of volatile compounds associated with 'green' sensory characters in Shiraz wine made from grapes grafted on Ramsey and Dog Ridge rootstocks. These wines were higher in this character compared to wines from Merbein 6262, a low vigour rootstock. GC‐olfactometry identified the compound responsible for this intense 'green' aroma to be 3‐isobutyl‐2‐methoxypyrazine, which was not detected in Shiraz grape berries but was found at significantly higher concentration in rachis tissue from bunches grown on Ramsey rootstock compared to own‐roots. Conclusions: Grape rachis inclusion is the most probable cause of the 3‐isobutyl‐2‐methoxypyrazine concentration in the Shiraz wines, and rootstocks can influence the accumulation of methoxypyrazines in the rachis. Significance of the Study: Methoxypyrazines in rachis tissues have the potential to impart 'green' sensory characters in wines of cultivars not known to produce methoxypyrazines in the berries. Other volatile aroma compounds were found to be affected by rootstocks which may also be useful in targeting rootstocks to give a desired wine style.